The Development of Interactive Digital Books Based on Kvisoft Flipbook Maker in Choral Subject - Firdhani, Aldhila Mifta; Heldisari, Hana Permata Heldisarib (Universitas Negeri Makassar, 2023)
The aim of Research and development is to create Interactive Digital Books that can be used as worthiness Online Learning Source in Choral 2nd level Subject, Music Education Program, Jakarta State University. This Research used Development of Borg & Gall Model with 5 stages (desire analysis, plan, design, development, and practice). Alfa Testing involved 4 experts while Beta Testing involved 52 students. Data is gathered by using questionnaire and then analyzed by using quantitative-descriptive technique and T-Testing. The Research show that this Digital Interactive Book: (1) worthiness score by media expert is 4.78 or